Neutralizing Antibodies in Persistent Borna Disease Virus Infection: Prophylactic Effect of gp94-Specific Monoclonal Antibodies in Preventing Encephalitis - Furrer, Esther (American Society for Microbiology, 2001)
Borna disease virus (BDV) infection triggers an immune-mediated encephalomyelitis and results in a persistent infection. The immune response in the acute phase of the disease is characterized by a cellular response in which CD8(+) T cells are responsible for the destruction of virus-infected brain cells. CD4(+) T cells function as helper cells and support the production of antiviral antibodies. Antibodies generated in the acute phase of the disease against the nucleoprotein and the phosphoprotein are nonneutralizing. In the chronic phase of the disease, neutralizing antibodies directed against the matrix protein and glycoprotein are synthesized. In the present work, the biological role of the neutralizing-antibody response to BDV was further investigated. By analyzing the blood of rats infected intracerebrally with BDV, a highly neurotropic virus, nucleic acid could be detected between 30 and 50 days after infection. Neutralizing antibodies were found between 60 and 100 days after infection. Furthermore, we produced hybridomas secreting BDV-specific neutralizing monoclonal antibodies. These antibodies, directed against the major glycoprotein (gp94) of BDV, were able to prevent Borna disease if given prophylactically. These data suggest that the late appearance of BDV-specific neutralizing antibodies is due to the presence of BDV in the blood of chronically infected rats. Furthermore, these antibodies have the potential to neutralize the infectious virus when given early, which is an important finding with respect to the development of a vaccine.